Design, synthesis, and bioevaluation of 1h-pyrrolo[3,2-c]pyridine derivatives as colchicine-binding site inhibitors with potent anticancer activities - Chao Wang; Yujing Zhang; Shanbo Yang; Lingyu Shi; Rong Rong; Tingting Zhang; Yudong Wu; Dongming Xing (Journal of Enzyme Inhibition and Medicinal Chemistry)
A new series of 1H-pyrrolo[3,2-c]pyridine derivatives were designed and synthesised as colchicine-binding site inhibitors. Preliminary biological evaluations showed that most of the target compounds displayed moderate to excellent antitumor activities against three cancer cell lines (HeLa, SGC-7901, and MCF-7) in vitro. Among them, 10t exhibited the most potent activities against three cancer cell lines with IC50 values ranging from 0.12 to 0.21 μM. Tubulin polymerisation experiments indicated that 10t potently inhibited tubulin polymerisation at concentrations of 3 μM and 5 μM, and immunostaining assays revealed that 10t remarkably disrupted tubulin microtubule dynamics at a concentration of 0.12 μM. Furthermore, cell cycle studies and cell apoptosis analyses demonstrated that 10t at concentrations of 0.12 μM, 0.24 μM, and 0.36 μM significantly caused G2/M phase cell cycle arrest and apoptosis. The results of molecular modelling studies suggested that 10t interacts with tubulin by forming hydrogen bonds with colchicine sites Thrα179 and Asnβ349. In addition, the prediction of physicochemical properties disclosed that 10t conformed well to the Lipinski’s rule of five.